Scaling the wall: overcoming barriers to STEM knowledge mobilization - Wilkins, Matthew R.; Rapciak, Stephanie E.; Goller, Carlos C.; Weintraub, Jory; Mikaelyan, Aram (Frontiers in Communication, 2024)
Improving science literacy is crucial amidst global challenges like climate change, emerging diseases, AI, and rampant disinformation. This is vital not only for future STEM generations but for all, to make informed decisions. Informal science communication efforts such as podcasts, popular science articles, and museum events are an essential part of the infrastructure for mobilizing knowledge and nurturing science literacy. However, in this Perspective, we emphasize the need to grow our capacity for STEM outreach in the formal K-12 classroom. While the majority of informal outreach mechanisms require audience members to seek out content, classrooms include those hard-to-reach target audiences that are not already STEM-engaged. We contrast the multitude of resources that have been developed to support informal outreach in recent decades with a relative paucity of such efforts in the K-12 formal classroom realm. We advocate for a more balanced deployment of resources and efforts between these two vital components of our knowledge mobilization and STEM engagement infrastructure. In particular, we highlight the key role of K-12 teachers as conduits for knowledge dissemination and the need for greater collaboration between scientists and teachers at individual and organizational levels. We also advocate for greater collaboration across programs in both the informal and formal outreach space, and dedicated effort to construct dissemination networks to share outreach materials at scale across disparate programs. The aim of our piece is to generate discussion about how we might refocus goals, funding mechanisms, and policies to grow the science-engaged society necessary to confront future challenges.